A Muragan [white woman]’s journey: Learning from Elders on Country how to support cultural understandings of non-First Nations educators through thearts ... - Macdonald, Jacqueline (University of Southern Queensland, 2024)
Research has revealed that it can be problematic for non-First Nations educators to embed the Aboriginal and Torres Strait Islander Histories and Cultures Cross-Curriculum Priority (CCP) as required in the nationally endorsed Australian Curriculum (AC) (Bishop & Vass, 2021; Stern & Burgess, 2021). This is related to a range of factors, including limited professional development resulting in low teacher self-efficacy (Gibson & Ewing, 2020; Lane, 2020). The Arts provide important opportunities for students to learn about and celebrate the diversity of human experience (Dissanayake, 2000, 2015). As an arts educator, I could see the potential of utilising the arts to support educators in engaging with and building their knowledge of the histories and cultures of Australia’s First Nations Peoples, with a particular focus on the local context of the school site. Through this research, a Participatory Action Research (PAR) project with the arts as a key central theme and a specific focus on the AC arts ...